Structural effects of sprifermin in knee osteoarthritis: a post-hoc analysis on cartilage and non-cartilaginous tissue alterations in a randomized controlled trial - Roemer, Frank; Aydemir, Aida; Lohmander, Stefan; Crema, Michel D.; Marra, Monica Dias; Muurahainen, Norma; Felson, David T.; Eckstein, Felix; Guermazi, Ali (BMC Musculoskeletal Disorders, 2016)
A recent publication on efficacy of Sprifermin for knee osteoarthritis (OA) using quantitatively MRI-defined central medial tibio-femoral compartment cartilage thickness as the structural primary endpoint reported no statistically significant dose response. However, Sprifermin was associated with statistically significant, dose-dependent reductions in loss of total and lateral tibio-femoral cartilage thickness. Based on these preliminary promising data a post-hoc analysis of secondary assessment and endpoints was performed to evaluate potential effects of Sprifermin on semi-quantitatively evaluated structural MRI parameters. Aim of the present analysis was to determine effects of sprifermin on several knee joint tissues over a 12 month period.1.5 T or 3 T MRIs were acquired at baseline and 12 months follow-up using a standard protocol. MRIs were read according to the Whole-Organ Magnetic Resonance Imaging Score (WORMS) scoring system (in 14 articular subregions) by four muskuloskeletal radiologists independently. Analyses focused on semiquantitative changes in the 100 ?g subgroup and matching placebo of multiple MRI-defined structural alterations. Analyses included a delta-subregional and delta-sum approach for the whole knee and the medial and lateral tibio-femoral (MTFJ, LTFJ), and patello-femoral (PFJ) compartments, taking into account number of subregions showing no change, improvement or worsening and changes in the sum of subregional scores. Mann-Whitney - Wilcoxon tests assessed differences between groups.Fifty-seven and 18 patients were included in the treatment and matched placebo subgroups. Less worsening of cartilage damage was observed from baseline to 12 months in the PFJ (0.02, 95 % confidence interval (CI) (-0.04, 0.08) vs. placebo 0.22, 95 % CI (-0.05, 0.49), p = 0.046). For bone marrow lesions (BMLs), more improvement was observed from 6 to 12 months for whole knee analyses (-0.14, 95 % CI (-0.48, 0.19) vs. placebo 0.44, 95 % CI (-0.15, 1.04), p = 0.042) although no significant effects were seen from the baseline visit, or in Hoffa-synovitis, effusion-synovitis, menisci and osteophytes.In this post-hoc analysis cartilage showed less worsening from baseline to 12 months in the PFJ, and BMLs showed more improvement from 6 to 12 months for the whole knee.ClinicalTrials.gov identifier: NCT01033994 .
EVALuna2:14636